Competência em informação nas organizações aprendentes: um estudo com os docentes do curso de direito da Universidade Estadual da Paraíba – Campus III - Araújo, Milena Borges Simões de (2017)
The complexity of legal information makes it necessary to realize your digital access and use your sources of legal information effectively, an unquestionable and pressing requirement. Based on this reality, the present study aims to analyze the information competence of teachers of the Campus III Law course of the State University of Paraíba regarding access to and use of legal information sources. It considers that the legal professors need this competence, since the Institutions of Higher Education are responsible for the academic production and for the appearance of new juridical information that influence in the practice of research of these professionals, which refers to the following questions: as do law school teachers seek to meet their information needs? What sources of information are most used by legal professors? In methodological terms, this is a field research, exploratory and descriptive, de-limited by the qualitative and quantitative approaches. As an instrument of data collection, an online questionnaire was used, and data were analyzed by the content analysis method in a sample of 18 participants. In addressing the information competence, we sought to provide a study that can bring practical and theoretical contributions, encouraging the discussions and the development of studies related to legal information. The results showed that the teachers participating in the research indicated that they are holders of most of the skills related to informational competence, verified from the conceptual basis and the information competence model The Seven Pillars. Therefore, the need for expansion and the development of other skills of this model has been concluded, which requires actions to improve access to and use of legal information. In order to meet the demands raised from the research results, systematic actions of information competence are suggested in order to achieve positive results, with amplification beyond the academic environment.